Role of Elm1, Tos3, and Sak1 Protein Kinases in the Maltose Metabolism of Baker’s Yeast - Yang, Xu; Meng, Lu; Lin, Xue; Jiang, Huan-Yuan; Hu, Xiao-Ping; Li, Cong-Fa (Frontiers in Microbiology, 2021)
Glucose repression is a key regulatory system controlling the metabolism of non-glucose carbon source in yeast. Glucose represses the utilization of maltose, the most abundant fermentable sugar in lean dough and wort, thereby negatively affecting the fermentation efficiency and product quality of pasta products and beer. In this study, we focused on the role of three kinases Elm1, Tos3, and Sak1 in the maltose metabolism of baker’s yeast in lean dough. The results suggest that overexpression of ELM1, TOS3, and SAK1 exerted different influence in the maltose metabolism of baker’ yeast with differential regulation of genes MAL61 and MAL62. ELM1 overexpression improved the maltose utilization and lean dough leavening capacity of baker’ yeast to a certain degree with an increased expression of MAL61. However, overexpression of TOS3 and SAK1 alone performed a negative effect on the maltose metabolism with the down-regulated transcription of MAL61/MAL62. These results for the first time suggest that Elm1 rather than Tos3 and Sak1 might be the dominant regulator in the Snf1-mediated glucose repression of maltose. The three upstream kinases might regulate maltose metabolism via Snf1-parallel pathways with a carbon source-dependent manner. These findings provide knowledge about the glucose repression of maltose and give a new perspective for the breeding of industrial yeasts with rapid maltose metabolism.